Bioactive Glass Granules Inhibit Mature Bacterial Biofilms on the Surfaces of Cochlear Implants. Issue 10 (December 2018) - Höing, Benedikt; Kirchhoff, Lisa; Arnolds, Judith; Hussain, Timon; Buer, Jan; Lang, Stephan; Arweiler-Harbeck, Diana; Steinmann, Joerg
Abstract : Hypothesis: Biofilm formation on cochlear implant (CI) surfaces differs between bacterial species and can be reduced by the application of S53P4 bioactive glass. Background: The formation of bacterial biofilms on medical devices, such as cochlear implants, can lead to chronic infections resulting in the need for implant removal. In this study, various surfaces of three CI implant kits from different manufacturers were examined for bacterial biofilm formation and reduction of a pre-existing biofilm by the application of bioactive glass. Methods: Biofilm formations of 4 bacterial species causing implant-related infections were tested on 17 different surfaces: Pseudomonas aeruginosa (ATCC9027), Staphylococcus aureus (ATCC6538), Staphylococcus epidermidis (ATCC12228), and Streptococcus pyogenes (ATCC19615). For P. aeruginosa and S. aureus biofilm reduction after application of S53P4 bioactive glass was evaluated. Results: All tested microbial species formed biofilms on the examined CI surfaces in a strain-dependent manner. For S. aureus, a significantly higher biofilm formation on metal components compared with silicone was found whereas the other strains did not show a material specific biofilm formation. Application of S53P4 bioactive glass resulted in a significant reduction of P. aeruginosa and S. aureus mature biofilm. Conclusion: The four bacteria species displayed biofilm formation on the CI surfaces in a species- and material-specific manner. The results show that bioactive glass can reduce biofilm formation on CI materials in vitro. Future studies are necessary to confirm the results in vivo.